2010
DOI: 10.1177/1545968309357925
|View full text |Cite
|
Sign up to set email alerts
|

People Preferentially Increase Hip Joint Power Generation to Walk Faster Following Traumatic Brain Injury

Abstract: Reduced gait speed following TBI appears to be attributable to biomechanical deficiencies such as reduced ankle power generation rather than reduced postural stability and increased caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 24 publications
6
43
0
Order By: Relevance
“…In contrast to TBI gait where cadence and step length were not significantly different to HCs at a matched speed [3], this cohort of people with TBI used a significantly higher cadence and shorter step length to attain a matched running speed. When asked to walk at faster gait speeds, people with TBI have demonstrated their ability to increase cadence and step length [34]. However, these results indicate the ability to further increase affected step length for running appears to be limited.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast to TBI gait where cadence and step length were not significantly different to HCs at a matched speed [3], this cohort of people with TBI used a significantly higher cadence and shorter step length to attain a matched running speed. When asked to walk at faster gait speeds, people with TBI have demonstrated their ability to increase cadence and step length [34]. However, these results indicate the ability to further increase affected step length for running appears to be limited.…”
Section: Discussionmentioning
confidence: 97%
“…These variables were generated from a review of known gait abnormalities following TBI, the key gait variables for normal walking and running and specific variables which have been identified as problematic in other neurological populations [3,33]. Several additional kinetic variables were also prioritized, based on the recent findings of Williams et al [34] which showed people with TBI compensate for distal power generation deficits with increased hip power generation when walking at faster gait speeds. Only data for participants capable of performing the walking and running trials are reported here.…”
Section: Methodsmentioning
confidence: 99%
“…Because the plantarflexor's roles of body support and forward propulsion are not independent (McGowan et al, 2009), the provision of external BWS should also reduce forward propulsion and subsequently step length for a given walking speed. Available data, however, either indicate no change in step length with BWS (Burgess et al, 2010;van Hedel et al, 2006) or contradict this assertion (McGowan et al, 2008;Threlkeld et al, 2003), suggesting that gait compensations occur at other important joints, such as the hip flexors (Nadeau et al, 1999;Williams et al, 2010). Understanding the biomechanical changes (e.g., forward propulsion and step lengths) with BWS is important to properly retrain abberant movement patterns in individuals who exhibit distal muscle weakness.…”
Section: Introductionmentioning
confidence: 90%
“…Nine kinematic measures of pelvic, hip, knee, and ankle movements, together with foot progression, were collated. The mean performance of five trials for each patient's kinematic trace for each of the nine parameters was compared to the average values obtained from a sample of 10 (5 male) healthy controls (Williams et al, 2010), walking at a speed which was slow, yet adequate for community ambulation (Perry et al, 1995). The mean age of the healthy control sample was 27.3 years (range 18-35 years).…”
Section: Discussionmentioning
confidence: 99%
“…The 3DGA was performed at the Centre for Health, Exercise and Sports Medicine, School of Physiotherapy, The University of Melbourne, using a previously described approach (Williams et al, 2010). Four additional markers were placed on a small thermoplastic plate positioned over the sacrum and secured with a firm pelvic support strap (Barrere Pelvic Strap model 384).…”
Section: Data Collectionmentioning
confidence: 99%